Amorphous NiCu Thin Films Sputtered on TiO2 Nanotube Arrays: A Noble‐Metal Free Photocatalyst for Hydrogen Evolution. Issue 23 (11th November 2022) - Pinna, Marco; Wei, Angeline Wo Weng; Spanu, Davide; Will, Johannes; Yokosawa, Tadahiro; Spiecker, Erdmann; Recchia, Sandro; Schmuki, Patrik; Altomare, Marco
Abstract: In this work, NiCu co‐catalysts on TiO2 are studied for photocatalytic hydrogen evolution. NiCu co‐catalyst films are deposited at room temperature by argon plasma sputtering on high aspect‐ratio anodic TiO2 nanotubes. To tune the Ni : Cu atomic ratio, alloys of various compositions were used as sputtering targets. Such co‐catalyst films are found to be amorphous with small nanocrystalline domains. A series of parameters is investigated, i. e., i) Ni : Cu relative ratio in the sputtered films, ii) NiCu film thickness, and iii) thickness of the TiO2 nanotube layers. The highest photocatalytic activity is obtained with 8 μm long TiO2 nanotubes, sputter‐coated with a 10 nm‐thick NiCu films with a 1 : 1 Ni : Cu atomic ratio. This photocatalyst reaches a stable hydrogen evolution rate of 186 μL h −1 cm −2, 4.6 and 3 times higher than that of Ni‐ and Cu‐TiO2, respectively, demonstrating a synergistic co‐catalytic effect of Ni and Cu in the alloy co‐catalyst film. Abstract : A photocatalyst consisting of an amorphous NiCu thin film sputtered on anodic TiO2 nanotubes is studied for photocatalytic hydrogen evolution. A performance improvement of 4.6 and 3 times compared to photocatalysts modified with pure Ni or pure Cu films is achieved due to synergistic effect of Ni and Cu in the bimetallic co‐catalyst layer.